Corchorus olitorius extract exhibit anti-hyperglycemic and anti-inflammatory properties in rodent models of obesity and diabetes mellitus - Mokgalaboni, Kabelo; Phoswa, Wendy Nokhwezi (Frontiers in Nutrition, 2023)
Obesity and type 2 diabetes (T2D) are chronic conditions with detrimental impacts on the overall health of individuals. Presently, the use of pharmacological agents in obesity and T2D offers limited benefits and pose side effects. This warrant studies on remedies that are less toxic and inexpensive while effective in ameliorating secondary complications in obesity and T2D. Plant-based remedies have been explored increasingly due to their remarkable properties and safety profile. We searched for pre-clinical evidence published from inception until 2023 on PubMed, Scopus, Google, and Semantic scholar on Corchorus olitorious (C.olitorious) in both obesity and T2D. Our focus was to understand the beneficial impact of this plant-based remedy on basic glycaemic, lipid, inflammatory, and biomarkers of oxidative stress. The evidence gathered in this review suggests that C.olitorius treatment may significantly reduce blood glucose, body weight, total cholesterol, triglycerides, and low-density lipoprotein (LDL) in concomitant with increasing high-density lipoprotein-cholesterol (HDL-c) in rodent models of obesity and T2D. Interestingly, this effect was consistent with the reduction of malonaldehyde, superoxide dismutase and catalases, tumour necrosis factor-alpha, interleukins, and leptin. Some of the mechanisms by which C.olitorius reduces blood glucose levels is through stimulation of insulin secretion, increasing β-cell proliferation, thus promoting insulin sensitivity; the process which is mediated by ascorbic acid present in this plant. C.olitorius anti-hyperlipidaemia is attributable to the content of ferulic acid found in this plant, which inhibits 3-Hydroxy-3-methyl glutaryl coenzyme A (HMG-CoA) reductase inhibitors and thus results in reduced synthesis of cholesterol and increased hepatic LDL-c receptor expression respectively. The present review provides extensive knowledge and further highlights the potential benefits of C.olitorius on basic metabolic parameters, lipid profile, inflammation, and oxidative stress in rodent models of obesity and T2D.